2021
DOI: 10.1073/pnas.2017092118
|View full text |Cite
|
Sign up to set email alerts
|

Placental trophoblast syncytialization potentiates macropinocytosis via mTOR signaling to adapt to reduced amino acid supply

Abstract: During pregnancy, the appropriate allocation of nutrients between the mother and the fetus is dominated by maternal–fetal interactions, which is primarily governed by the placenta. The syncytiotrophoblast (STB) lining at the outer surface of the placental villi is directly bathed in maternal blood and controls feto–maternal exchange. The STB is the largest multinucleated cell type in the human body, and is formed through syncytialization of the mononucleated cytotrophoblast. However, the physiological advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…Abnormal formation or function of STB during pregnancy may hinder material and gas exchange between the mother and the foetus and thus impair foetal growth, implicating in the aetiology of pregnancy complications, such as preeclampsia and foetal growth restriction. 42 This may be the reason for the low foetal weight in this COVID‐RS case. In addition, HLA‐C and HLA‐G in the EVT subset, which is critical to establish protective immunity at the maternal–foetal interface, are downregulated in COVID‐RS placenta, indicating the impairment in immune tolerance to the foetus.…”
Section: Discussionmentioning
confidence: 85%
“…Abnormal formation or function of STB during pregnancy may hinder material and gas exchange between the mother and the foetus and thus impair foetal growth, implicating in the aetiology of pregnancy complications, such as preeclampsia and foetal growth restriction. 42 This may be the reason for the low foetal weight in this COVID‐RS case. In addition, HLA‐C and HLA‐G in the EVT subset, which is critical to establish protective immunity at the maternal–foetal interface, are downregulated in COVID‐RS placenta, indicating the impairment in immune tolerance to the foetus.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, in amino acid-deficient environments, mTORC1 is dissociated from lysosomes, preventing its function as a metabolic hub to promote various anabolic processes (Efeyan, Zoncu and Sabatini, 2012). Inhibition of mTORC1 in human trophoblasts was recently shown to enhance macropinocytosis (Shao et al, 2021). GCN2 or mTORC1 may regulate CSF1R expression at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the syncytiotrophoblast (ST) to perform macropinocytosis has been shown in recent studies [ 56 ]. It has been reported that about 10% of trophoblast cells from term placentas could be infected in vitro with VacV [ 57 ].…”
Section: Variola Virusmentioning
confidence: 99%